Characteristics of male and female injecting drug users of the AjUDE-Brasil II Project - Ana Maria de Oliveira Cintra; Waleska Teixeira Caiaffa; Sueli Aparecida Mingoti
The object of this study is to compare female and male injection drug users (IDUs) in terms of sociodemographic profile and aspects of their initiation to the use of injection drugs. It was a cross-sectional and multicentric study realized in 2000-2001 in six Brazilian syringe-exchange programs. 146 women and 709 men were interviewed, with average ages of 29.5 and 28.3 years, respectively. Both began injection drug use at similar ages, 18.6 and 19.3, for women and men, respectively, although women report more frequently than men that they were initiated by a sexual partner to acquiring drugs and syringes, and to the act of injection. Compared to men, women report significantly more regular sexual partners (83% versus 72%); fewer casual partners (39% versus 58%), more use of injection drugs with their partners, as well as more "exchange" of sex for drugs. Among HIV-seropositive individuals, women show less education, had more chance of their sexual partners participating in their initiation to injection drugs, and report sexual partners that used injection drugs more frequently. Female IDUs exhibit aspects of behavior indicating greater vulnerability to HIV infection than do males.